Perilous desert : insecurity in the Sahara - Wehrey, Frederic M.; Boukhars, Anouar (Carnegie Endowment for International Peace, 2013)
The geopolitical significance of the Sahara is becoming painfully clear. Islamist militant groups and transnational criminal networks are operating in the region's most fragile states, exploiting widespread corruption, weak government capacity, crushing poverty, and entrenched social and ethnic tensions. The unrest spills over borders and aggravates protracted regional crises. This insecurity raises urgent concerns for the broader Sahara and the West. Perilous Desert details the sources of instability and what can be done to minimize the threat of simmering conflicts. L.